2014
DOI: 10.1016/j.ecresq.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Playing with others: Head Start children's peer play and relations with kindergarten school competence

Abstract: Time-sampled observations of Head Start preschoolers' (N = 264; 51.5% boys; 76% Mexican American; M = 53.11 and SD = 6.15 months of age) peer play in the classroom were gathered during fall and spring semesters. One year later, kindergarten teachers rated these children's school competence. Latent growth models indicated that, on average, children's peer play was moderately frequent and increased over time during preschool. Children with higher initial levels or with higher slopes of peer play in Head Start ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 59 publications
2
35
0
3
Order By: Relevance
“…In this play therapy program, using Gurney approach (a combination of family therapy and child-centered play therapy), the researcher was not only able to enjoy the results of action research, but also study the effects of indigenous games in the form of Gurney approach (the customized play therapy training package), on the parents of ADHD preschoolers. The findings of the present study were in line with those of various related studies, including Pearson (2008), Nair, Yusof, and Arumugam (2014), Yang, Tai, Yang, and Gau (2013), Halperin, and Healey (2011), Barkley (2013), Vural, Akkaya, Küçükparlak, Ercan, and Eracar (2014), Eggum-Wilkens et al (2014). These studies showed that play therapy increases the family's positive performance and decreases clinical symptoms of ADHD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this play therapy program, using Gurney approach (a combination of family therapy and child-centered play therapy), the researcher was not only able to enjoy the results of action research, but also study the effects of indigenous games in the form of Gurney approach (the customized play therapy training package), on the parents of ADHD preschoolers. The findings of the present study were in line with those of various related studies, including Pearson (2008), Nair, Yusof, and Arumugam (2014), Yang, Tai, Yang, and Gau (2013), Halperin, and Healey (2011), Barkley (2013), Vural, Akkaya, Küçükparlak, Ercan, and Eracar (2014), Eggum-Wilkens et al (2014). These studies showed that play therapy increases the family's positive performance and decreases clinical symptoms of ADHD.…”
Section: Discussionsupporting
confidence: 81%
“…The developmental abilities and compatibility of children who had participated in the head start program and played with their peers had increased (Eggum-Wilkens et al, 2014). Using the intervention program of behavior therapy of parents of preschool children with ADHD (Huang et al, 2009) reduces parents' internalizing and externalizing behavior problems in the posttest step.…”
Section: Introductionmentioning
confidence: 99%
“…According to compelling ECE research studies (e.g., Eggum-Wilkens et al 2014;Gmitrová and Gmitrov 2003), the framework argued that children learn best in supportive environments that encourage exploration and discovery through play and interaction. This perspective was in stark contrast with the tradition of many kindergartens in Singapore, whose main goal was to prepare students for the Primary One curriculum (Khoo 2010).…”
Section: Preschool Education In Singapore: the Learning Areas For Holmentioning
confidence: 99%
“…Iermakova [6,7], О.М. Ionova [8][9][10][11][12][13], М. Knyazieva [14], L. Melnichuk [16], Eggum-Wilkens N.D. [23], Halle T.G. [25] concerning role of administrator in increasing of educational-teaching process's effectiveness.…”
Section: Results Of the Researchmentioning
confidence: 99%